MSMEs as the Backbone of the Economy: Optimizing Potential and Facing Various Challenges - Nurhabits Safitri; Arina Dinana; Mashudi (Public Service: Jurnal Ilmu Sosial dan Pendidikan, 2025)
Micro, Small, and Medium Enterprises (MSMEs) play a strategic role in the national economy, particularly as job providers and economic growth drivers. Their contribution to Gross Domestic Product (GDP) and the equitable distribution of community welfare makes MSMEs the backbone of the economy. However, this sector still faces various challenges, including access to capital, digitalization, global competitiveness, and regulations that are not yet fully supportive. This article discusses the significant potential of MSMEs in supporting the national economy and the optimization strategies that can be applied, such as increasing financial access, utilizing digital technology, and strengthening business partnerships. With the right policy support and cross-sector collaboration, MSMEs can further develop and provide more significant contributions to the Indonesian economy.